(untitled) (Polish Yearbook of International Law, 2023)
This research aims to present and analyse selected issues of Polish return law and practice in the light of the European Union return policy and against the backdrop of the migration crises of 2015 and 2021-2023, with a return decision placed at the heart of the study. The principal research objective is to examine whether the provisions of the 2013 Act on Foreigners follow the standards established in the EU Return Directive as well as in the case-law of the Court of Justice of the European Union. Another objective is to analyse the interaction between the provisions forming the uniform national return policy, but which originate from different legal systems (national and European ones). To this end “anti-terrorism” and “pushback” cases under Polish law will be assessed. The article thus poses several crucial questions, inter alia whether the Polish law and practice comply with standards established at the European level, especially insofar as fundamental rights of individuals are concerned; whether they contribute to the establishment of an effective EU return policy; and what role harmonisation plays in this process.